Research progress on the mechanism and markers of metabolic disorders in the occurrence and development of cognitive dysfunction after ischemic stroke - Li, Huaqiang; Ke, Xiaohua; Feng, Bianying; Tian, Huan; Cai, Zhenzhen; Zhang, Anren; Man, Qiuhong (Frontiers in Endocrinology, 2025)
Post-stroke cognitive impairment (PSCI) is a common complication following a stroke that significantly affects patients’ quality of life and rehabilitation outcomes. It also imposes a heavy economic burden. There is an urgent need to better understand the pathophysiology and pathogenesis of PSCI, as well as to identify markers that can predict PSCI early in the clinical stage, facilitating early prevention, monitoring, and treatment. Although the mechanisms underlying PSCI are complex and multifaceted, involving factors such as atherosclerosis and neuroinflammation, metabolic disorders also play a critical role. This article primarily reviews the relationship between metabolic disorders of the three major nutrients—sugar, fat, and protein—and the development of cognitive dysfunction following ischemic stroke (IS). It aims to elucidate how these metabolic disturbances contribute to cognitive dysfunction post-stroke and to explore potential metabolic biomarkers for PSCI. We believe that this review will offer new insights into the early identification, treatment, and prognostic assessment of PSCI.